Increasing isotropy and predictability through electroplating of tensile properties of polyamide 12 parts manufactured by selective laser sintering - Slager, Jonathan J.; Earp, Brian C.; Storck, Steven M.; Wise, Sean; Zupan, Marc; Ibrahim, Ahmed M. (Progress in Additive Manufacturing, 2026)
Additive manufacturing is rapidly evolving and finding a place in nearly every industry. Recent advances make selective laser sintering especially well positioned to rapidly create complex parts with material properties capable of withstanding rigorous end use applications. However, these properties still pale in comparison to their metal powder bed fusion counterparts and can be plagued by anisotropy due to print orientation. This can be especially true for large parts with relatively thin structural walls. Combining selective laser sintering with metal electroplating has shown promise to increase both strength and isotropy. While traditional metal–polymer hybrid composites have struggled to maintain consistent properties across varying geometries, this work demonstrates control over material properties at scales previously not possible, enabling a new class of lightweight structures with improved survivability. This novel research has experimentally found the tensile properties and isotropy of different electroplating coatings and investigates techniques that can be used to increase coating adhesion and uniformity over the rough non-conductive printed part surface. It is shown that though both the printed and electroplated material are individually anisotropic, the combination of printing and subsequent electroplating can improve overall build direction isotropy. This research represents a shift in additive manufacturing by transforming what was once considered a limitation of SLS printing—thin-wall anisotropy—into an opportunity for creating customized material properties through strategic metal deposition but also opens up new design spaces where minimum weight and minimum volume design trajectories are needed.